Evaluation of lymph node reactivity in differentiated thyroid carcinoma - Amar, Ali; Rapoport, Abrão; Rosas, Marilene Paladino (São Paulo Medical Journal, 1999)
CONTEXT: The development of metastases is the most notable characteristic of malignant neoplasias. The filter function of lymph nodes, which led to the idea of including lymphatic treatment in surgical management of metastases. OBJECTIVES: To evaluate morphological alterations in neck nodes in the presence of differentiated thyroid carcinoma (DTC): hyperplasia, histiocytosis, desmoplasia, capsular rupture, necrosis and their relation to the biological behavior of these neoplasias. DESIGN: Retrospective study. SETTING: University referral unit. PARTICIPANTS: 98 DTC patients, from 1977 to 1992, 18 cases were selected for histological analyses, of which 14 were female and 4 males, with an average age of 50.2 years. From these cases, 290 lymph nodes were analyzed (81 with metastasis), with an average of 16 lymph nodes/patient. MAIN MEASUREMENTS: Morphological evaluation of paraffin cuts stained by HE was done using an optical microscope, looking for presence of the abovementioned neoplasias and their UICC-TNM (1997) staging. RESULTS: Sinus histiocytosis was 2.4 times more frequent in the absence of lymph node metastasis (pNo). Disease recurrence occurred in 5 patients, all of whom were more than 40 years old (p= 0.24) and 4 of whom had necrosis (p= 0.02). Six patients with predominance of paracortical hyperplasia (p= 0.02) did not show as much relapse into disease as those with less than 6 metastasis lymph nodes (p= 0.009). CONCLUSIONS: The presence of paracortical hyperplasia is associated with a better prognosis. The existence of necrosis or metastasis in more than 6 lymph nodes in patients over 40 years of age is related to higher risk of relapse of disease in DTC.